Peningkatan Literasi Gizi Untuk Pencegahan Anemia Pada Remaja Melalui Edukasi Interaktif Di Sma Papua Kasih Kota Jayapura - Juenita Elfunam Mado; Sri Iriyanti; Dorci Nuburi; Since Kadiwaru; Rosmaida Sirait; Margaretha O. Deda (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Iron deficiency anemia among high school adolescents in the Papua region has become a critical public health issue, with a national prevalence of 15.5%. This condition is driven by low nutrition literacy, unbalanced dietary patterns, and its negative impact on academic performance and immunity. This community service program aims to improve nutrition literacy for anemia prevention through interactive education at SMA Papua Kasih as the partner institution, targeting 30 adolescent students. A mixed-methods approach was applied, including a pretest–posttest questionnaire (20 items, Cronbach’s Alpha >0.7), participatory observation, in-depth interviews, and secondary data analysis using SPSS Paired t-test and NVivo. The results showed a significant increase in nutrition literacy, with the proportion of students in the low–moderate category decreasing to 55.3% and those with good knowledge rising to 85.7%, as indicated by a Paired t-test result of p<0.001. Additionally, active student participation reached 93%, and 87% of participants reported that the interactive learning approach helped them better understand anemia prevention and apply healthier dietary habits in their daily lives. This program demonstrates that interactive nutrition education can effectively enhance adolescents’ nutrition literacy and serves as a strategic effort to reduce the risk of iron deficiency anemia in high school populations, particularly in the Papua region.